Radical learning through semantic transformation: Capitalizing on novelty. Issue 1 (February 2016) - Bosma, Bas; Chia, Robert; Fouweather, Ian
That organizations exist in a fluid environment of unprecedented and discontinuous change seems beyond debate. We seem to find ourselves immersed in a world in which events have a tendency to unfold and overtake us in unforeseeable and novel ways that defy comprehension; a crisis of meaning takes place and conventional sensemaking is disrupted. Our need to imaginatively construct new meanings that allow us to understand what is going on and to work out how to respond becomes ever more pressing. We do live in interesting times. The emergence of the new, however, challenges current established ways of knowing and opens a creative space for radical learning to take place. Novelty stimulates the generative process by which organizations and individuals learn, adapt to, and cope with the exigencies they face in order to survive and progress. Such radical learning occurs when creative linguistic interventions in dialogue open up semantic spaces whereby new terms are coined and old ones broken up, combined, and/or redeployed in novel ways, in an effort to give expression to the fresh circumstances experienced or new phenomena observed. We call this kind of imaginative linguistic intervention semantic transformation . In this article, we argue that it is this semantic transformation that promotes radical transformational learning. Such semantic transformation is predicated on the improvisatory character of dialogue as a form of communication. We explore how, through this dialogical process of semantic transformation, we discover the resources and means to respond to the vagueness and equivocality experienced, by exploiting language in novel ways in our attempts to make sense of and account for such experiences.